2015
DOI: 10.1242/bio.20149654
|View full text |Cite
|
Sign up to set email alerts
|

Can crayfish take the heat?Procambarus clarkiishow nociceptive behaviour to high temperature stimuli, but not low temperature or chemical stimuli

Abstract: Nociceptors are sensory neurons that are tuned to tissue damage. In many species, nociceptors are often stimulated by noxious extreme temperatures and by chemical agonists that do not damage tissue (e.g., capsaicin and isothiocyanate). We test whether crustaceans have nociceptors by examining nociceptive behaviours and neurophysiological responses to extreme temperatures and potentially nocigenic chemicals. Crayfish (Procambarus clarkii) respond quickly and strongly to high temperatures, and neurons in the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 61 publications
(79 reference statements)
4
29
0
Order By: Relevance
“…However, this panel also raised the point that pain and distress in crustaceans may occur by placing animals in cold water and heating the water to boiling point. More recent studies of crayfish by Puri and Faulkes [ 76 ] confirmed the presence of nociceptors responsive to heat, but did not find evidence of nociceptive responses to low temperatures. The same panel and the RSPCA [ 23 ] also states that all crustaceans should be immersed in ice slurry for at least 20 min to reach unconsciousness whereas here we demonstrate that for crayfish and shrimps a few seconds are enough to anesthetize them.…”
Section: Discussionmentioning
confidence: 99%
“…However, this panel also raised the point that pain and distress in crustaceans may occur by placing animals in cold water and heating the water to boiling point. More recent studies of crayfish by Puri and Faulkes [ 76 ] confirmed the presence of nociceptors responsive to heat, but did not find evidence of nociceptive responses to low temperatures. The same panel and the RSPCA [ 23 ] also states that all crustaceans should be immersed in ice slurry for at least 20 min to reach unconsciousness whereas here we demonstrate that for crayfish and shrimps a few seconds are enough to anesthetize them.…”
Section: Discussionmentioning
confidence: 99%
“…These include grooming by prawns of antennae stimulated with low- or high-pH saline ( Barr et al, 2008 ) (although another study failed to find such responses in three decapod crustaceans) ( Puri and Faulkes, 2010 ); grooming-like responses, escape, and withdrawal after stimulation of the mouth or eyes of crabs with acetic acid ( Elwood et al, 2017 ); and defensive responses to touching crayfish claws or antennae with a hot probe ( Puri and Faulkes, 2015 ). Tentative electrophysiological evidence for crustacean nociceptors came from recordings of increased ongoing afferent activity in crayfish antennal nerves during application of hot saline ( Puri and Faulkes, 2015 ). However, the observed increase in activity was modest and the small volume applied in the bath might not have been sufficient to heat antennal receptors to noxious levels.…”
Section: Immediate Responses To Noxious Stimulation In Crustaceansmentioning
confidence: 99%
“…Thus, studies found that fruit flies (Drosophila melanogaster) possess nociceptors that mediate behavioural responses to noxious stimuli (Tracey et al, 2003;Kim et al, 2012). Similarly, crayfish (Procambarus clarkii) possess sensory neurons that respond specifically to noxious high temperatures, while not to low temperatures, and these neural responses were accompanied by behavioural responses (Puri and Faulkes, 2015). Prawns (Palaemon elegans) rub their antennae when pinched or treated with certain chemicals (Barr et al, 2008 The present document has been produced and adopted by the bodies identified above as author(s).…”
Section: Nociception and Potential Pain In Invertebratesmentioning
confidence: 99%